2013
DOI: 10.1007/s10899-013-9419-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impulsivity and Sensation-Seeking Mediators of the Psychological Consequences of Pathological Gambling in Adolescence

Abstract: Pathological gambling has severe consequences for adolescents and their families and friends. Despite its high prevalence, pathological gambling in adolescents has been insufficiently studied. Sensation seeking and impulsivity are two variables that are related to the appearance and maintenance of pathological gambling. However, few studies have determined the role these variables play in the development of the dysfunctional symptomatology of gambling behavior in adolescents and young adults. The aims of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 44 publications
3
28
0
5
Order By: Relevance
“…These results confirm the findings of previous studies demonstrating that among both adolescents and adults anxiety and depression co-occur with problematic gambling (Blaszczynski and McConaghy, 1989; Coman et al, 1997; Raylu and Oei, 2002; Kim et al, 2006; Barrault and Varescon, 2013; Martin et al, 2014; Estevez et al, 2015; Chinneck et al, 2016; Cunningham et al, 2016; Toneatto and Pillai, 2016; see also, Takamatsu et al, 2016). It may be that depression foregoes problem gambling, which serves to relieve negative emotions and to avoid problems (Blaszczynski and Nower, 2002) or that problematic gambling involvement increasingly leads to depressive symptoms due to the consequent social isolation and money problems (Dussault et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…These results confirm the findings of previous studies demonstrating that among both adolescents and adults anxiety and depression co-occur with problematic gambling (Blaszczynski and McConaghy, 1989; Coman et al, 1997; Raylu and Oei, 2002; Kim et al, 2006; Barrault and Varescon, 2013; Martin et al, 2014; Estevez et al, 2015; Chinneck et al, 2016; Cunningham et al, 2016; Toneatto and Pillai, 2016; see also, Takamatsu et al, 2016). It may be that depression foregoes problem gambling, which serves to relieve negative emotions and to avoid problems (Blaszczynski and Nower, 2002) or that problematic gambling involvement increasingly leads to depressive symptoms due to the consequent social isolation and money problems (Dussault et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…With regard to self-reported impulsivity traits, a recent study using exploratory factor analyses found higher BIS-11 Motor Impulsiveness, Attentional Impulsiveness, and Non-planning Impulsiveness in PGs versus healthy controls27. Elevated dimensions of impulsivity (i.e., Negative Urgency, Positive Urgency, Motor Impulsiveness, Attentional Impulsiveness, and Non-planning Impulsiveness) in our non-clinical sample of PG are in keeping with the present literature27316768. Furthermore, at-risk PG individuals (i.e., ARGs) in our study also showed higher levels of these traits (except Non-planning Impulsiveness), while ARGs and PGs were not differentiated on these dimensions of impulsivity (except Positive Urgency), which supports the notion that elevated impulsiveness in PG (Negative Urgency, Motor Impulsiveness, Attentional Impulsiveness in the present study) may not stem from the disorder itself as the harmful effects of recurrent gambling52.…”
Section: Discussionsupporting
confidence: 90%
“…Está basado en el MULTICAGE CAD-4, cuestionario de cribado de conductas compulsivas, con y sin sustancias (Pedrero-Pérez et al, 2007), que ha sido utilizado en atención primaria (Garrido-Elustondo, Reneses, Navalón, Martín, Ramos y Fuentes, 2016; Reneses et al, 2015; Rodríguez-Monje, Pedrero-Pérez, Fernández-Girón, Gallardo-Alonso y Sanz-Cuesta, 2009), adicciones comportamentales (Estevez, Herrero-Fernández, Sarabia y Jauregui, 2015; Estévez Gutiérrez, Herrero Fernández, Sarabia Gonzalvo y Jáuregui Bilbao, 2014) y adicción a sustancias (Navas, Torres, Cándido y Perales, 2014;Martínez-Gonzá-lez, Munera-Ramos y Becoña-Iglesias, 2013;Pedrero-Pérez, 2010). Esta nueva versión formula cuatro preguntas, con respuesta dicotómica (SÍ/NO), por cada conducta problema, interrogando: ítem 1, estimación de exceso en la dedicación temporal; ítem 2, estimación de otros significativos; ítem 3, dificultad para no realizar la conducta; ítem 4, dificultades en interrumpir voluntariamente la conducta.…”
Section: Instrumentosunclassified